2001
DOI: 10.1111/j.1349-7006.2001.tb01084.x
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of the Multidrug Resistance Protein 3 in Drug Sensitivity and Its Expression in Human Glioma

Abstract: The multidrug resistance protein (MRP) family belongs to the ATP-binding cassette superfamily (ABC) of transporters, which are involved in ATP-dependent transport of hydrophobic compounds. One of the MRP family, MRP1, is partially associated with the multidrug resistance phenotype in brain tumors. In this study, we asked whether another MRP family gene, MRP3, could affect drug sensitivity to anticancer agents in human glioma cell lines and clinical glioma specimens. We first produced two antisense transfectant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
31
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 25 publications
6
31
0
Order By: Relevance
“…The apparent induction of MRP1 protein expression noted in late-stage tumors would seem to support this notion; i.e., 90% of tumor cells showed positive MRP1 staining in glioblastoma multiform (grade IV) versus less than 10% staining in grade II oligodendrogliomas (Benyahia et al, 2004). Likewise, significant up-regulation of MRP1 and MRP3 has also been demonstrated in malignant gliomas (anaplastic astrocytomas and glioblastomas), compared with epileptic control tissue or low-grade astrocytomas (Haga et al, 2001;Spiegl-Kreinecker et al, 2002). Interestingly, at least one immunohistochemical study failed to detect significant amounts of MRP3 protein in human glioma samples, despite the presence of high MRP3 gene levels (Bronger et al, 2005).…”
Section: B Brain Cancermentioning
confidence: 52%
See 1 more Smart Citation
“…The apparent induction of MRP1 protein expression noted in late-stage tumors would seem to support this notion; i.e., 90% of tumor cells showed positive MRP1 staining in glioblastoma multiform (grade IV) versus less than 10% staining in grade II oligodendrogliomas (Benyahia et al, 2004). Likewise, significant up-regulation of MRP1 and MRP3 has also been demonstrated in malignant gliomas (anaplastic astrocytomas and glioblastomas), compared with epileptic control tissue or low-grade astrocytomas (Haga et al, 2001;Spiegl-Kreinecker et al, 2002). Interestingly, at least one immunohistochemical study failed to detect significant amounts of MRP3 protein in human glioma samples, despite the presence of high MRP3 gene levels (Bronger et al, 2005).…”
Section: B Brain Cancermentioning
confidence: 52%
“…Mohri et al (2000) observed both MRP1 mRNA and protein expression in 50 and 90% of chemotherapy-naive grade III anaplastic astrocytomas and grade IV glioblastomas, respectively (see Kleihues et al, 1993, for a review of the World Health Organization tumor classification system). Expression of MRP1 in low-grade astrocytomas has not been consistently observed, suggesting that MRP1 expression in grade II gliomas is probably near the detection limit of the assays used (Abe et al, 1998;Mohri et al, 2000;Haga et al, 2001). The apparent induction of MRP1 protein expression noted in late-stage tumors would seem to support this notion; i.e., 90% of tumor cells showed positive MRP1 staining in glioblastoma multiform (grade IV) versus less than 10% staining in grade II oligodendrogliomas (Benyahia et al, 2004).…”
Section: B Brain Cancermentioning
confidence: 99%
“…In our study, we observed that combined treatment of glioma cells with chemotherapy drug TMZ and CDK6 shRNA significantly inhibited cell growth, which is more effective than single treatment either with TMZ or CDK6 shRNA. The mechanism underlying chemotherapy-resistance of glioma has been intensively studied (18,19,21,22). Many drugresistant genes have been found, which mainly belongs to DNA repair enzymes, small-molecule transmembrane transporters and drug metabolism proteins.…”
Section: Discussionmentioning
confidence: 99%
“…al. (55) investigated the expression level of members of the MRP family. They found no difference in the expression level of P-glycoprotein and MRP2 between normal brain and malignant glioma cells.…”
Section: The Bbb In Primary or Metastatic Brain Tumorsmentioning
confidence: 99%